2019
DOI: 10.1101/781716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signaling Diversity Enabled by Rap1-Regulated Plasma Membrane ERK with Distinct Temporal Dynamics

Abstract: A variety of different signals induce specific responses through a common, ERK-dependent kinase cascade. It has been suggested that signaling specificity can be achieved through precise temporal regulation of ERK activity. Given the wide distrubtion of ERK susbtrates across different subcellular compartments, it is important to understand how ERK activity is temporally regulated at specific subcellular locations. To address this question, we have expanded the toolbox of FRET-based ERK biosensors by creating a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(73 reference statements)
2
2
0
Order By: Relevance
“…Second, we simulated Ras or Rap knockout and measured ERK activity after LTP induction. Simulation results are consistent with experimental data (Grewal et al, 2000b, 2000a; Keyes et al, 2020; Li et al, 2016; Takahashi et al, 2013; York et al, 1998; Zhang et al, 2018) as knocking out Rap1 produces a greater ppERK deficit than knocking out Ras (Figure 8 - Supplementary Figure 3B). We assessed whether Ras could compensate for Rap and vice versa, by doubling the quantity of the remaining GTPase.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Second, we simulated Ras or Rap knockout and measured ERK activity after LTP induction. Simulation results are consistent with experimental data (Grewal et al, 2000b, 2000a; Keyes et al, 2020; Li et al, 2016; Takahashi et al, 2013; York et al, 1998; Zhang et al, 2018) as knocking out Rap1 produces a greater ppERK deficit than knocking out Ras (Figure 8 - Supplementary Figure 3B). We assessed whether Ras could compensate for Rap and vice versa, by doubling the quantity of the remaining GTPase.…”
Section: Resultssupporting
confidence: 85%
“…Thus, our model predicts that an Epac knockout would lead to slower ERK activation. These different time frames of ERK may phosphorylate different targets (Keyes et al, 2020; Zhai et al, 2013; Zhang et al, 2018). For example, Epac, a molecule of emerging importance in neurodevelopmental disorders, may have a role in disorders in cAMP degradation by enhancing the early activation of ERK.…”
Section: Resultsmentioning
confidence: 99%
“…For example, using Förster Resonance Energy Transfer (FRET)-based ERK biosensors, Keyes et al showed that EGF induces sustained ERK1/2 activity near the plasma membrane in contrast to the transient activity observed in the cytoplasm and in the nucleus. This supports the concept that the spatial and temporal regulation of ERK1/2 activity is integrated by the cell to control the specificity of signaling [36].…”
Section: Implications Of Phosphorylation In Mapk Erk1/2 Regulation In Time and Spacesupporting
confidence: 83%
“…In hematopoietic progenitors, Rap1 activation significantly enhanced ERK activation [57]. Also, EGF induced plasma membrane ERK activation, and cell morphology changes involve Rap1 [58]. C3G dependent signaling through activation of Rap is required for integrin-dependent adhesion [59].…”
Section: Discussionmentioning
confidence: 98%